Clinical signs and maternal and neonatal outcomes of pregnant women with Covid-19 hospitalized in the first and second wave of coronavirus in Golestan province - Roya Esmailpour Estarkhi; Narjes Sadat Borghei; Zahra Mehrbakhsh; Shima Rahimian (Mashhad University of Medical Sciences, 2022)
Introduction: Regarding to the pandemic of coronavirus and the existence of limited studies on the outcome of this disease in pregnant women, the present study was performed aimed to determine the clinical signs and outcomes of pregnant women with coronavirus. Methods: This descriptive study was performed on 100 pregnant women living in Golestan province who were infected with Covid-19 virus and were admitted to one of the hospitals in the Golestan province in 2020. All pregnant women who were hospitalized due to Covid-19 were followed up for two months after delivery. A researcher-made data collection form was used to evaluate the clinical signs and consequences of coronavirus. Data were analyzed by SPSS software (version 18). Results: The most common clinical sign in pregnant women was fever on the first day, and most women became asymptomatic from 4th day. Among the maternal consequences, 2 cases (2%) of maternal death was observed in the infected mothers. Preterm delivery (16%) and then oligohydramnios (8%) were more common. Most of the pregnant women did not have fetal complications. Among neonatal outcomes, neonatal hospitalization in the intensive care unit (30%) was the most common, and then neonatal jaundice (24%) and preterm infants (11%) were the most common reported cases. Also, 67% of women with Covid-19 had cesarean section delivery and the birth weight of 77% of infants was in the normal range. Conclusion: Covid-19 infection in pregnant women significantly increased adverse maternal and neonatal outcomes; therefore, better planning should be done to prevent this disease in pregnant women so that less pregnant women are affected.